Oxoperoxo tungsten(VI) complex immobilized on Schiff base-modified Fe3O4 magnetic nanoparticles as a heterogeneous catalyst for oxidation of alcohols with hydrogen peroxide. Issue 2 (17th January 2017) - Eftekhari-Sis, Bagher; Akbari, Masoud; Amini, Mojtaba; Ashouri, Fatemeh; Bagherzadeh, Mojtaba
Abstract: Oxoperoxo tungsten(VI) complex immobilized on Schiff base-modified Fe3 O4 super paramagnetic nanoparticles were synthesized and appropriately characterized using FT-IR, XRD, SEM, TEM, EDX, BET, and VSM analysis. The synthesized nanoparticles efficiently catalyzed oxidation of benzylic alcohols with H2 O2 as oxidant in high yields, with high to excellent selectivity. The catalyst can be recovered using an external magnetic field and recycled for subsequent oxidation reactions without any appreciable loss of efficiency. The simple preparation, high activity, excellent selectivity, and simple recoverability of the catalyst are advantageous. Abstract :